(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
This paper tackles the issue of the police interrogation of the suspect after implementation of the Directive 2013/48/EU on the right of access to a lawyer in criminal proceedings. Therefore, this paper first analyses the standards of the European Convention of Human Rights and European standards aimed at strengthening the procedural position of suspects in criminal proceedings. Then it introduces new provisions regulating police inquires of criminal offenses and powers and duties of the police during the formal interrogation of the suspect. Next, the paper considers the possibility of using the results of the police interrogation of suspects as a sufficient basis for filling the indictment, and points to some solutions in comparative law. Finally, the authors critically examine first rulings of Croatian courts on the sufficiency of police interrogation of suspect for filling the indictment and issuing a penalty order and in this regard, proposes possible solutions thereto de lege ferenda.